The effect of clinically relevant doses of immunosuppressive drugs on human mesenchymal stem cells - Javorkova, Eliska; Vackova, Julie; Hajkova, Michaela; Hermankova, Barbora; Zajicova, Alena; Holan, Vladimir; Krulova, Magdalena (Biomedicine & pharmacotherapy, 2018)
Immunosuppressive drugs are used to suppress graft rejection after transplantation and for the treatment of various diseases. The main limitations of their use in clinical settings are severe side effects, therefore alternative approaches are desirable. In this respect, mesenchymal stem cells (MSCs) possess a regenerative and immunomodulatory capacity that has generated considerable interest for their use in cell-based therapy. Currently, MSCs are tested in many clinical trials, including the treatment of diseases which require simultaneous immunosuppressive treatment. Since the molecular targets of immunosuppressive drugs are also present in MSCs, we investigated whether immunosuppressive drugs interact with the activity of MSCs. Human MSCs isolated from the bone marrow (BM) or adipose tissue (AT) were cultured in the presence of clinical doses of five widely used immunosuppressive drugs (cyclosporine A, mycophenolate mofetil, rapamycin, prednisone and dexamethasone), and the influence of these drugs on several factors related to the immunosuppressive properties of MSCs, including the expression of immunomodulatory enzymes, various growth factors, cytokines, chemokines, adhesion molecules and proapoptotic ligands, was assessed. Glucocorticoids, especially dexamethasone, showed the most prominent effects on both types of MSCs and suppressed the expression of the majority of the factors that were tested. A significant increase of hepatocyte growth factor production in AT-MSCs and of indoleamine 2,3-dioxygenase expression in both types of MSCs were the only exceptions. In conclusion, clinically relevant doses of inhibitors of calcineurin, mTOR and IMPDH and glucocorticoids interfere with MSC functions, but do not restrain their immunosuppressive properties. These findings should be taken into account before preparing immunosuppressive strategies combining the use of immunosuppressive drugs and MSCs.
Keywords: Immunomodulation; Immunosuppressive Agents; Interferon-gamma; Cell Proliferation; leukocyty mononukleární; vztah mezi dávkou a účinkem léčiva; interferon gama; Chemokine; kultivované buňky; Mesenchymal stem cell; Leukocytes, Mononuclear; lidé; Humans; Growth factor; Cytokine; Immunosuppressive drug; proliferace buněk; Cells, Cultured; Dose-Response Relationship, Drug; Mesenchymal Stem Cells; imunosupresiva; mezenchymální kmenové buňky